(untitled) (Medicine Today, 2022)
Introduction: Cement dust is emitted during the different steps of cement production. This dust is composed of chemical components that may have unfavourable effects on the haematological system. The workers in these factories are exposed daily to this toxic dust. Those exposed to the cement dust may suffer from changes in platelet count and eventually suffer from damaging effects on the cardiovascular system. Objective: Assess the effects of cement dust on platelet count of cement mill workers. Materials and Methods: Conduction of this cross sectional study took place in the Department of Physiology, Dhaka Medical College, Dhaka between July 2017 to June 2018. After fulfilling the ethical consideration, 46 apparently healthy male cement mill workers, working for 2 or more years in a cement mill , with range of age of 20 to 50 years (study group) and 46 BMI, age and socioeconomic condition matched apparently healthy male subjects from Dhaka city were control group. The platelet count was estimated using automated haematology analyzer in Dhaka Medical College Hospital, Dhaka. Data was collected in a pre-designed structured questionnaire form. Unpaired Student’s ‘t’ test and Pearson’s correlation coefficient test were performed for statistical analysis. Results: In this study, the platelet count was significantly (p < 0.05) higher than those of control group. The platelet count was directly related with duration of cement dust exposure. Conclusions: This study concludes that the cement dust has harmful effect on the platelet count and the duration of exposure to cement dust also has an effect on this parameter. Medicine Today 2022 Vol.34(1): 44-46